The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1055/s-0037-1608661
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Return to Sports in Patients with Chronic Achilles Tendon Rupture after Minimally Invasive Reconstruction with Semitendinosus Tendon Graft Transfer

Abstract: Objective  The purpose of the study is to evaluate the clinical results and return to sports in patients undergoing reconstruction of the Achilles tendon after minimally invasive reconstruction with semitendinosus tendon graft transfer. Methods  Eight patients underwent surgical reconstruction with a minimally invasive technique and tendon graft augmentation with ipsilateral semitendinosus tendon for chronic Achilles tendon rupture (more than 30 days after the injury and a gap of >6 cm). Patients were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Open and minimally invasive techniques using a semitendinosus graft, both allograft and autograft, have been described [ 14 , 22 , 25 , 36 , 40 , 43 ]. Those studies report ATRS scores between 86 and99.…”
Section: Discussionmentioning
confidence: 99%
“…Open and minimally invasive techniques using a semitendinosus graft, both allograft and autograft, have been described [ 14 , 22 , 25 , 36 , 40 , 43 ]. Those studies report ATRS scores between 86 and99.…”
Section: Discussionmentioning
confidence: 99%
“…This study provided an animal model for a reconstruction of the ITCL with an autograft of the semitendinosus. The semitendinosus is a regular autograft for tendon transplant [ 31 ]. One strand of it is similar to the ITCL in diameter and intensity according to the results of our study for ligamentous biomechanics [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future clinical trials should include kinesiophobia and fear avoidance beliefs as covariables to determine the clinical effectiveness of psychological or physical therapy treatments such as dry needling or ischemic compression in athletes suffering from gastrocnemius MPS [7,8]. In addition, the influence of fear of movement and fear avoidance beliefs should be considered in future studies about clinical outcomes or return to sports in athletes suffering from chronic gastrocnemius MPS and Achilles tendinopathies [7,55]. Finally, future studies should be carried out to determine foot orthoses' effectiveness in order to reduce kinesiophobia and fear avoidance beliefs in athletes with gastrocnemius MPS, as prior studies have shown a pain reduction in other musculoskeletal conditions such as low back pain [56], knee pain [57], forefoot pain [58], and rheumatoid arthritis [59].…”
Section: Future Studiesmentioning
confidence: 99%